(untitled) (Global Journals of Research in Engineering, 2012)
It is often required to compute the power consumed by an application to avoid later surprises of low battery life, or high temperature a device reaches while running the application; potentially damaging the device. There are three ways to find power consumed by a system for executing a particular application. 1) Run application on a reference board and measure the power dissipated. 2) Simulate the power consumed by the target system by running standard applications on it, but simulations can be time consuming. 3) Use heuristic formulas based on pre-analyzed simulation data. In this paper we come with some empirical formulas to calculate the power of a particular application, So that we do not need to run extensive simulations.